Injury Prevention: A Public Health Concern for India (Nepal Journal of Epidemiology, 2013)
The poor implementation of traffic rules & regulations, heterogeneous mixed traffic, poorly designed roads, traffic vehicles, increasing speed, poor use of protective device such as helmet, drinking and driving, poor visibility, and poor trauma care are a major concern in reducing the prevalence of injuries and related outcome5. Looking at the magnitude of the problems, strong public health emphasis is needed in the areas of research, policy development, community education and awareness, and the health care system in India.  DOI: http://dx.doi.org/10.3126/nje.v3i3.9189 Nepal Journal of Epidemiology 2013;3(3): 275-276